(untitled) - Aguirre, Adalberto (Boston, 2001)
This brief and inexpensive text provides a concise introduction to the dynamics of racial and ethnic relations. After summarizing key concepts and theories, the authors develop a simple theoretical framework that guides the presentation of data on each of the prominent ethnic groups in America. As a result, the book examines each ethnic group from the same perspective, allowing students to compare the dynamics of discrimination against African Americans, Native Americans, Asian Americans, white ethnics, and Latinos. Moreover, this framework provides a way to examine ethnic relations around the world and to compare the dynamics in other parts of the world with those operating in America.
Keywords: Discrimination,Ethnicity,United states,United states; Race relations,Ethnic relations; United states,United states